PENGARUH PEMBERIAN ASAP CAIR PADA BERBAGAI KONSENTRASI TERHADAP PERTUMBUHAN Streptococcus mutans PENYEBAB KARIES GIGI - Meiliza Ariesti C. Hutauruk; Gunawan Wibisono; V. Rizke Ciptaningtyas (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background: The main requirement for the forming of caries is the plaque on the mouth. Bacteriahave a vital role in causing caries and periodontal. Streptococcus mutans is considered to have a vital role in causing caries. This research used liquid smoke solution which has antibacterial effect.Aim: Knowing the effect of the application of liquid smoke solution at various concentrations on the growth of S. mutans and determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC).Methods: This research is experimental research with post test only control group design. The sample used the colony of S. mutans. In this research, there were six sample groups and one control group.The sample’s given was by applying the liquid smoke solutions with 100%, 50%, 25%, 12,5%, 6,25%, and 0% concentration levels towards the research samples.The data was obtained by visually observing the growth of S. mutans colonies in each sample groups. Statistical test was using Kruskal-Wallis test and continued with Mann-Whitney test.Results: Result from the research shows the role of liquid smoke solutions in hindering the growth of S.mutans through its chemical components. Giving smoke liquid solution on 6,25 concentration can hold the growth of S.mutans bacteria and on 12,5 % concentration can kill the growth of S. mutans bacteria.Conclusion: Giving the smoke liquid solution on any concentration can give effect for the growth of S.mutans.